SymbioCity: reconceptualising the future of the shopping mall - Green, Warren Roland (My University, 2011)
Architecture, and the concept of produced space, cannot be divorced from the basic notion of society and, with this, social integration and social interaction. This thesis considers the massive potential, and missed opportunity, which the suburban shopping mall offers as a socio-economic community framework within the urban landscape. Malls have become principal sites of social communion while resisting adaptation to this new public agenda and have become disconnected from the city. Shopping has historically always been an open, public and social forum, forming an integrated part of society and the city. With the proliferation of the car and the consequent urban sprawl, however, retail has evolved into a typology that is an isolated and single-use phenomenon in the shape of the shopping mall. It is exclusive in its nature and context, and becomes a barrier to the notion of community, particularly in South Africa where this model seems to negate safety concerns but does not consider human dignity. The disconnection and lack of connectivity and access forces the architecture to become a themed space where branding is overriding and diversity is extremely limited. The public street has been privatised and becomes quasi-public; social interaction is forced to take place in a privately controlled pseudo-urban environment that turns its back on the city and the scale and texture of urbanity becomes eroded. Urban planning and current legislation permit these massive single-use forms to develop, allowing fragmented spatial and social proximities to occur without the benefit of the synergies of uses that take place as happens in naturally evolving cities. The introduction of a complimentary mix of uses will allow the mall to become a truly integrated and city-like resource. The current model is also unsustainable when viewed holistically in terms of the balanced triumvirate of economy, environment and equity, known as the ‘triple bottom line’. The mall creates a massive carbon footprint and, as part of the existing produced stock that functions well as a commercial model, needs to adapt to contemporary social and environmental needs, as well as those of the future. Opportunities for symbiotic relationships will be explored and will be introduced wherein there is a mutual and beneficial sharing of resources of both the mall and the city around it. The malls’ current form is one wherein resources are both heavily consumes and wasted. Symbiosis will form a vital and integral paradigm for looking at a mixeduse intervention where the retail, in the form of the mall, once again forms an integrated part of the city and feeds back into it. The mall will become a symbiotic typology, deriving from and linking into the urban fabric, becoming the street again, from where its roots are derived. This symbiotic paradigm will be further extended within all systems of the intervention and the mall will now become a generator of resources as apposed to its current form as a consumer of resources. Keywords: shopping, urbanity, typology, quasi-public, street, unsustainable, symbiosis QUESTION I will be dealing with the concept of the shopping mall and the inherent dichotomy of public and private space. With this, the social consequences of the suburban model as a private retail spatial phenomenon that appropriates part of the city to itself and the question of how we reconceptualise its future through symbiotic relationships in order that it relinquishes this space back to the city and the public.